Burundi : Statistical Annex. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
The following statistical data of Burundi are presented in detail: savings and investment, cotton production, consumption, exports, and prices, production of manufacturing industries, energy production, imports, and consumption, retail prices of petroleum products, minimum wages, import duty exemptions, military expenditure, central government revenue, structure of interest rates, composition of exports and imports, services and transfers, list of public enterprises, structure, volume, and prices of international trade, direction of trade, summary of exchange and trade system, size, composition, and so on.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet